2023
DOI: 10.3390/ijms24043381
|View full text |Cite
|
Sign up to set email alerts
|

RNAseq Analysis of FABP4 Knockout Mouse Hippocampal Transcriptome Suggests a Role for WNT/β-Catenin in Preventing Obesity-Induced Cognitive Impairment

Abstract: Microglial fatty-acid binding protein 4 (FABP4) is a regulator of neuroinflammation. We hypothesized that the link between lipid metabolism and inflammation indicates a role for FABP4 in regulating high fat diet (HFD)-induced cognitive decline. We have previously shown that obese FABP4 knockout mice exhibit decreased neuroinflammation and cognitive decline. FABP4 knockout and wild type mice were fed 60% HFD for 12 weeks starting at 15 weeks old. Hippocampal tissue was dissected and RNA-seq was performed to mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 177 publications
0
1
0
Order By: Relevance
“…In microglia, the immune cells of the brain, exposure to dietary saturated fatty acids triggers a shift towards active inflammatory phenotypes. We have previously shown that a high fat diet (HFD) leads to increased hippocampal microgliosis and cognitive decline in mice [9,10]. As neuroinflammation and microglial activation are factors implicated in the etiology of AD [11], we hypothesize that proinflammatory activation of brain microglia in obese young adult mice exacerbates AD pathology and increases accumulation of the amyloid beta (Aβ) plaques characteristic of AD [6].…”
Section: Introductionmentioning
confidence: 99%
“…In microglia, the immune cells of the brain, exposure to dietary saturated fatty acids triggers a shift towards active inflammatory phenotypes. We have previously shown that a high fat diet (HFD) leads to increased hippocampal microgliosis and cognitive decline in mice [9,10]. As neuroinflammation and microglial activation are factors implicated in the etiology of AD [11], we hypothesize that proinflammatory activation of brain microglia in obese young adult mice exacerbates AD pathology and increases accumulation of the amyloid beta (Aβ) plaques characteristic of AD [6].…”
Section: Introductionmentioning
confidence: 99%